Agency and Communion From the Perspective of Self Versus Others: The Moderating Role of Social Class - Chen, Xiaochen; Li, Muzi; Wei, Qingwang (Frontiers in Psychology, 2019)
Communion and agency are the two fundamental dimensions of social perception. The dual perspective model (DPM) predicts that communion is more desirable and important in the other-perspective, whereas agency is more desirable and important in the self-perspective. Social class psychology has suggested that social class is also systematically linked to one’s orientation toward communion and agency. However, little is known about how basic perspectives (i.e., self versus other) and social class jointly affect the primacy of communion and agency in social cognition. The current study attempted to address this gap by asking participants from different social class conditions to rate the importance of communal and agentic traits both with respect to the self and to another person. Results indicated that lower-class individuals rated communal traits as more important than agentic ones for others, whereas upper-class individuals rated agentic traits as more important than communal ones for themselves. This work extends both DPM and the social class psychology. Current findings could provide important practical implications for inter-class communications.